Systemic therapy for laryngeal carcinoma - Thorsten Fuereder; Florian Kocher; Jan Baptist Vermorken; Jan Baptist Vermorken (Frontiers in Oncology)
Laryngeal squamous cell carcinoma (LSCC) accounts for 100,000 deaths worldwide each year. Despite multimodal treatment, outcomes for both high-risk locally advanced and recurrent/metastatic laryngeal carcinoma remain poor. Treatment intensification through induction chemotherapy has not improved overall survival, although it may contribute to larynx preservation. Consequently, multiple recent efforts have been made to integrate novel immunotherapies into the current treatment algorithm for LSCC. In particular, perioperative immunotherapy regimens appear to be the most promising approach for preserving laryngeal function and optimizing event-free and overall survival rates in the locally advanced setting. In the recurrent/metastatic setting, the 5-year overall survival rate is approximately 20% with pembrolizumab-based regimens. Primary and secondary resistance to immunotherapy is frequently observed in the majority of patients. Along with trials of checkpoint inhibitor monotherapy, combinatorial approaches with novel immunotherapies, bispecific antibodies, targeted therapies, and antibody-drug conjugates are being explored for the treatment of recurrent/metastatic laryngeal carcinoma. This article aims to discuss recent efforts to improve outcomes and quality of life for patients with locally advanced and recurrent/metastatic LSCC.